Comparative transcriptomic analysis reveals key components controlling spathe color in Anthurium andraeanum (Hort.). - Jaime A Osorio-Guarín; David Gopaulchan; Corey Quanckenbush; Adrian M Lennon; Pathmanathan Umaharan; Omar E Cornejo (PLoS ONE, 2021)
Anthurium andraeanum (Hort.) is an important ornamental in the tropical cut-flower industry. However, there is currently insufficient information to establish a clear connection between the genetic model(s) proposed and the putative genes involved in the differentiation between colors. In this study, 18 cDNA libraries related to the spathe color and developmental stages of A. andraeanum were characterized by transcriptome sequencing (RNA-seq). For the de novo transcriptome, a total of 114,334,082 primary sequence reads were obtained from the Illumina sequencer and were assembled into 151,652 unigenes. Approximately 58,476 transcripts were generated and used for comparative transcriptome analysis between three cultivars that differ in spathe color ('Sasha' (white), 'Honduras' (red), and 'Rapido' (purple)). A large number of differentially expressed genes (8,324), potentially involved in multiple biological and metabolic pathways, were identified, including genes in the flavonoid and anthocyanin biosynthetic pathways. Our results showed that the chalcone isomerase (CHI) gene presented the strongest evidence for an association with differences in color and the highest correlation with other key genes (flavanone 3-hydroxylase (F3H), flavonoid 3'5' hydroxylase (F3'5'H)/ flavonoid 3'-hydroxylase (F3'H), and leucoanthocyanidin dioxygenase (LDOX)) in the anthocyanin pathway. We also identified a differentially expressed cytochrome P450 gene in the late developmental stage of the purple spathe that appeared to determine the difference between the red- and purple-colored spathes. Furthermore, transcription factors related to putative MYB-domain protein that may control anthocyanin pathway were identified through a weighted gene co-expression network analysis (WGCNA). The results provided basic sequence information for future research on spathe color, which have important implications for this ornamental breeding strategies.